2012
DOI: 10.1088/0964-1726/21/2/025006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the dielectric properties of polyacrylate dielectric elastomer

Abstract: The dielectric constant of elastomeric dielectric material is an essential physical parameter, whose value may affect the electromechanical deformation of a dielectric elastomer actuator. Since the dielectric constant is influenced by several external factors as reported before, and no certain value has been confirmed to our knowledge, in the present paper, on the basis of systematical comparison of recent past literature, we conducted extensive works on the measurement of dielectric properties of VHB films, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 46 publications
3
59
0
2
Order By: Relevance
“…This allowed actuated area strains of 15 % -35 % to be achieved. Moreover, pre-stretching has been shown to be the key to developing large strains in these materials [21][22][23]. In an elastomer, the mobility of molecular chains can be restrained by intermolecular interactions [24].…”
Section: Fig 1 the Working Principle Of A Dementioning
confidence: 99%
See 1 more Smart Citation
“…This allowed actuated area strains of 15 % -35 % to be achieved. Moreover, pre-stretching has been shown to be the key to developing large strains in these materials [21][22][23]. In an elastomer, the mobility of molecular chains can be restrained by intermolecular interactions [24].…”
Section: Fig 1 the Working Principle Of A Dementioning
confidence: 99%
“…However, it is reasonable for a DE to obtain a larger deformation at a pre-stretch ratio where the composite exhibits a minimum elastic modulus for the introduction of a constant electric field. It has been shown that a higher voltage-induced strain can be achieved by imposing an equi-biaxial pre-stretch on a film instead of applying a uniaxial pre-stretch [28,21]. However, most research into the mechanical properties of DEs was carried out using the conventional uniaxial tensile test [29,11].…”
Section: Fig 1 the Working Principle Of A Dementioning
confidence: 99%
“…However, for a dielectric elastomer, the voltage-actuated strain is often limited by pull-in instability (electromechanical instability) [20] and electrical breakdown. As the applied voltage is increased, the thickness of the polymer decreases, so that this same applied voltage induces an even higher electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Поэтому, посколь-ку электрическое поле в материале зависит от его теку-щей конфигурации, это имеет принципиальное значение для определения предельной деформации, совместимой с данным электрическим полем, и наоборот. В то же время можно считать общепризнанным [4], что величина электрической прочности в случае кратковременных и высокоинтенсивных электрических воздействий значи-тельно отличается от статического случая, а также зависит от материала электродов, их геометрии, размера и конфигурации межэлектродного промежутка [5,6], кон-такта между полимерным образом и электродами. Таким образом, зависимость между электрической прочностью и степенью деформации эластомера оказывается под влиянием совокупности факторов.…”
unclassified
“…Благодаря высокой диэлек-трической проницаемости (до ε r = 6) в классе ДЭ и возможности обратимой деформации более 100% дан-ный материал широко применяется для устройств на основе ДЭ, и, как следствие, он служит модельным ма-териалом при исследовании поведения диэлектрических эластомеров в условиях высоких напряжений и больших деформаций [5][6][7]. Лента VHB размещалась между плоскими торцами стальных цилиндрических электродов (∅ 5 mm).…”
unclassified